Regional variability and solubility of apolipoprotein E in brains from patients with Alzheimer's and Parkinson's disease: Human neuropathology/proteinopathies. (7th December 2020) - Twohig, Daniel; Karampatsi, Dimitra; Edlund, Anna K.; Nielsen, Henrietta M.
Abstract: Background: APOE ε 4 is the strongest genetic risk factor for both Alzheimer's disease (AD) and dementia with Lewy bodies (DLB), and increases the severity of Lewy pathology in Parkinson's disease (PD) and DLB 1 . Interestingly, nearly all familial PSEN1 mutation‐carrying AD patients exhibit Lewy pathology specifically in the amygdala 2 and higher CSF α‐synuclein levels in APOE ε 4 ‐carrying asymptomatic familial AD patients were linked to amyloid‐β pathology 3 . Further, brain‐area specific intraneuronal accumulation of soluble α‐synuclein was previously reported in AD patients 4 and an enrichment of ApoE was described in dopaminergic neurons of PD patients 5 . Together the accumulating evidence suggests an intricate interplay between APOE ε 4, ApoE and α‐synuclein in both PD/DLB and AD. Here we investigated the levels and molecular size distribution of ApoE4 and total ApoE in three different brain areas from PD and AD patients. Method: Fresh‐frozen tissue (Netherlands Brain Bank) from the medial frontal lobe, medial temporal lobe and amygdala of neuropathologically confirmed AD (n=3) and PD (n=3) patients with an APOE ε 3/ ε4 genotype was lysed and fractionated to yield tris‐buffered saline (TBS) soluble and TBS‐Triton X‐100 (TBX) soluble protein fractions. Western blotting, densitometry and statistical analysis were then used to identify, quantify and compare levels of total ApoE and ApoE4 in the two fractions from each brain area. Result: TBS‐soluble levels of monomeric ApoE4 were higher in PD patients versus AD patients specifically within the amygdala (p=0.046), the same fractions also contained high molecular weight ApoE bands (90‐95kDa) that were significantly enriched in the AD patients (p=0.028) The TBX‐soluble fractions from the frontal gyrus of PD patients exhibited lower levels of fragmented (28‐30kDa) ApoE4 (p=0.047) and total ApoE compared to AD patients. Conclusion: Elevated levels of TBS‐soluble monomeric ApoE4 in the amygdala of PD patients compared to AD patients and increased fragmentation of TBX‐soluble ApoE and specifically ApoE4 in AD patients together suggest an implication of ApoE4‐specific processes that differ between PD and AD.